2014
DOI: 10.1103/physrevb.89.045413
|View full text |Cite
|
Sign up to set email alerts
|

Andreev reflection in monolayer MoS2

Abstract: Andreev reflection in a monolayer molybdenum disulfide superconducting-normal (S/N) hybrid junction is investigated. We find, by using a modified-Dirac Hamiltonian and the scattering formalism, that the perfect Andreev reflection happens at normal incidence with p-doped S and N regions. The probability of the Andreev reflection and the resulting Andreev conductance, in this system, are demonstrated to be large in comparison with the corresponding gapped graphene structure. We further investigate the effect of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 32 publications
(40 reference statements)
4
36
2
Order By: Relevance
“…We have found that the presence of the mass asymmetry term (α) in the Hamiltonian of MoS 2 has no significant effect on the charge conductance of the CT and CAR processes (similar behavior has been demonstrated for AR process in Ref. [57]). Therefore, we set α = 0 in our investigations.…”
Section: A Charge Conductancesupporting
confidence: 77%
“…We have found that the presence of the mass asymmetry term (α) in the Hamiltonian of MoS 2 has no significant effect on the charge conductance of the CT and CAR processes (similar behavior has been demonstrated for AR process in Ref. [57]). Therefore, we set α = 0 in our investigations.…”
Section: A Charge Conductancesupporting
confidence: 77%
“…Moreover, we find that the presence of the mass asymmetry term (α) in the Hamiltonian of MoS 2 has no significant effect on the valley-and spin-resolved conductances (similar behaviors have been demonstrated for local and nonlocal AR processes in Refs. [28,29]). …”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Also, the single-layer and multi-layer MoS 2 can be n-or p-type doped on generating desirable charge carriers [7,8]. Recently, the properties of the charge, spin and valley transport in a monolayer molybdenum disulfide p/n/p [27], ferromagnetic/superconducting/ferromagnetic (F/S/F) [28] and normal/superconducting (N/S) [29] junctions have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Here, motivated by experimental and some theoretical studies [16][17][18][19][20][21][22], we investigate the Josephson effect through the ML-MoS 2 both at its normal and spin-polarized (magnetic) states. If we induce conventional s-wave superconductivity in ML-MoS 2 via proximity, the Cooper pairs are formed from excitations from different (opposite) valleys and having opposite spins, very similar to the case of graphene [23].…”
mentioning
confidence: 99%